Study of quantum well solar cells based on CuIn1-xGaxSe2 absorbers using SCAPS-1D simulator - SALAMANI Maram safàa; BEDDIAR Abdrrahmen; ENCA/BOUCHAMA Idris (UNIVERSITY OF M’SILA, 2025)
This thesis presents a comprehensive numerical study of Cu(In₁₋ₓGaₓ)Se₂ (CIGS)-based solar cells. It begins with a detailed examination of the structure, composition, and advantages of the CIGS material for photovoltaic applications. Using the SCAPS-1D simulator, several simulations are performed to assess the influence of key physical parameters—such as gallium content, absorber thickness, acceptor concentration, and defect density—on solar cell performance. The thesis also explores the integration of quantum well (QW) structures within the CIGS absorber. Numerical modeling of CIGS/QW devices evaluates the effect of quantum well thickness, defect levels, and well depth on the photovoltaic performance. The results provide valuable insights into optimizing CIGS-based solar cells, particularly through quantum engineering approaches.
Keywords: Solar cell; Cu(In; Ga)Se2 absorber; Quantum well; Substrate structures; QWSC